A hybrid transverse flux linear motor. - Misron, Norhisam (2010)

(untitled)
A hybrid transverse flux linear motor (100) is provided, the motor (100) includes a 3 phase magnetic circuit coupled to a stator (110), a plurality of movers (120) configurable such that flux flow from the 3 phase magnetic circuit is perpendicular to motion direction of the plurality of movers (120), wherein the plurality of movers (120) further include a plurality of coils (140) embeddable in the plurality of movers (120).